P-286 Notch Signaling and TNF-α Synergistically Up-regulate Stem Cell-Specific Genes, OLFM4 and UBD, in the Inflamed Intestinal Epithelia of IBD Patients. (February 2017) - Kawamoto, Ami; Nakata, Toru; Fujii, Satoru; Suzuki, Kohei; Ishibashi, Fumiaki; Tsuchiya, Kiichiro; Nakamura, Tetsuya; Okamoto, Ryuichi; Watanabe, Mamoru
Abstract : Background: The intestinal epithelium of inflammatory bowel disease (IBD) patients is exposed to various pro-inflammatory cytokines, the most important of which is TNF-α. We have previously shown that the Notch signaling pathway is also up-regulated in the intestinal epithelial cells (IECs) of such mucosa, and contributes to IEC proliferation and mucosal regeneration. However, it is not known how these 2 elements interact to influence the fate of IECs in IBD; whether they synergize or otherwise antagonize for the acquirement of a specific IEC property. Thus we aimed to reproduce such an inflamed epithelial environment in vitro and explore the gene regulation at play, as well as study if these particular gene regulations are significant in the disease setting by analyzing surgical specimens taken from IBD patients. Methods: Microarray analysis was performed on a human colonic epithelial cell line LS174T where the Notch intracellular domain (NICD) was over-expressed by induction using Doxycycline, while TNF-α was simultaneously added. The expression levels of OLFM4 and UBD by IECs were analyzed by quantitative RT-PCR and western blot. The transcriptional activity of OLFM4 and UBD were measured by a gene-specific promoter-driven luciferase assay. Surgical tissues from the colon and small intestine of IBD patients were immunostained to compare the distribution of OLFM4 and UBD expression in inflamed and uninflamed states. Results: Microarray analysis revealed up to 21 genes that were synergistically up-regulated by combined NICD over-expression and addition of TNF-α. Among those genes, quantitative RT-PCR showed a significantly increased expression of OLFM4 and UBD on simultaneous NICD over-expression and addition of TNF-α in LS174T cells. Consistently, western blot showed both up-regulated OLFM4 and UBD protein expression after TNF-α addition to LS174T cells over-expressing NICD. Both OLFM4 promoter-driven and UBD promoter-driven luciferase assay showed significantly increased promoter activity on simultaneous NICD over-expression and addition of TNF-α in LS174T cells, revealing the expression of both OLFM4 and UBD to be regulated at the transcriptional level under these conditions. Accordingly, sustained and enhanced activation of the NF-kB pathway was observed by the simultaneous NICD over-expression and addition of TNF-α in LS174T cells, suggesting its involvement in the transcriptional up-regulation of OLFM4 and UBD. Immunostaining of uninflamed small intestinal and colonic tissues from IBD patients showed both OLFM4 and UBD expression to be limited to crypt base columnar stem cells, whereas an increased number of OLFM4 and UBD expressing IECs were seen in inflamed tissues, spanning whole crypts. Conclusions: The Notch signaling pathway and TNF-α synergistically up-regulate the expression of stem cell-specific genes, OLFM4 and UBD, in human IECs. The up-regulation of these genes might contribute to the protection and survival of IECs under the inflammatory environment, through their shared anti-apoptotic properties.